2017
DOI: 10.1016/j.apjtm.2017.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Synergists action of piperonyl butoxide and S,S,S-tributyl phosphorotrithioate on toxicity of carbamate insecticides against Blattella germanica

Abstract: In most of these strains, resistance to bendiocarb and carbaryl is completely eliminated by DEF, showing a very high role of estraze enzymes in resistance to bendiocarb and carbaryl. But in most strains PBO does not remove the resistance because other mechanisms, such as reduced cuticle penetration and insensitivity to the acetylcholine esterase enzyme, may be involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…This may be attributable to the application protocol utilized in this study or to the concentration at which PBO was applied. Numerous studies have shown that the efficacy of PBO as a synergist is dependent on the concentration at which it is applied (Hewlett, 1969;Guglielmone et al, 1999;Dehkordi et al, 2017;Nikpour et al, 2017). This is further evidenced by the inability of PBO to increase the toxicity of both type II pyrethroids screened in this study (deltamethrin and -cyfluthrin).…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributable to the application protocol utilized in this study or to the concentration at which PBO was applied. Numerous studies have shown that the efficacy of PBO as a synergist is dependent on the concentration at which it is applied (Hewlett, 1969;Guglielmone et al, 1999;Dehkordi et al, 2017;Nikpour et al, 2017). This is further evidenced by the inability of PBO to increase the toxicity of both type II pyrethroids screened in this study (deltamethrin and -cyfluthrin).…”
Section: Discussionmentioning
confidence: 99%
“…Эти данные указывают на участие MO в формировании толерантности к изученным карбаматам. В то же время ППБ не устраняет резистентность, что указывает на наличие других механизмов резистентности, таких как снижение проницаемости кутикулы для инсектицидов и нечувствительность ацетилхолинэстеразы [31]. Со-гласно нашим данным наиболее активным синергистом пропоксура оказался ТБТФ, однако величины КСД были значительно меньшими, чем в случае с хлорпирифосом.…”
Section: Discussionunclassified
“…Cockroaches have been adapted with the human life environments including hospitals [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . They can pose some risks to humans such as transfer of pathogens to humans which may cause serious illness.…”
Section: Introductionmentioning
confidence: 99%